Computational analysis for residue-specific CDK2-inhibitor bindings - Yang, Yun-peng; He, Li-ping; Bao, Jing-xiao; Qi, Yi-fei; Zhang, John Z. H. (Chinese journal of chemical physics, 2019)
Cyclin-dependent kinase 2 (CDK2) is a key macromolecule in cell cycle regulation. In cancer cells, CDK2 is often overexpressed and its inhibition is an effective therapy of many cancers including breast carcinomas, leukemia, and lymphomas. Quantitative characterization of the interactions between CDK2 and its inhibitors at atomic level may provide a deep understanding of protein-inhibitor interactions and clues for more effective drug discovery. In this study, we have used the computational alanine scanning approach in combination with an efficient interaction entropy method to study the microscopic mechanism of binding between CDK2 and its 13 inhibitors. The total binding free energy from the method shows a correlation of 0.76−0.83 with the experimental values. The free energy component reveals two binding mode in the 13 complexes, namely van der Waals dominant, and electrostatic dominant. Decomposition of the total energy to per-residue contribution allows us to identify five hydrophobic residues as hot spots during the binding. Residues that are responsible for determining the strength of the binding were also analyzed.